Author self-archiving in open access institutional repositories for awareness creation in universities - Kwame Kodua-Ntim (Cogent Social Sciences, 2024)
The study explored the authors self-archiving to create awareness of open access institutional repositories in universities. The study’s qualitative approach was informed by the interpretive paradigm and the case research design. The target population was all twelve (12) open access institutional repositories managers. Interviews were conducted using a semi-structured interview guide and data were analyzed using thematic analysis. The study revealed that author self-archiving could improve awareness of open access institutional repositories. The study recommended that universities fully implement the author’s self-archiving protocol, and the university and university library should provide rigorous policies and incentives for author self-archiving.